Coronary perfusion pressure as a determinant of ventricular performance - Tucci, P. J.; Spadaro, J.; Ciogna, A. C.; Bregagnollo, E. A. (Springer Nature, 1980)
The results observed in this work support the view that coronary perfusion pressure affects ventricular performance independently of metabolic effects; a mechanism operating in beat-to-beat regulation is proposed.
Keywords: animal experiment; coronary artery blood flow; dog; heart; heart ventricle contraction; isolated heart; Animal; Blood Pressure; Coronary Vessels; Dogs; Heart; In Vitro; Perfusion; Support, Non-U.S. Gov't